CdZnS Nanowire Decorated with Graphene for Efficient Photocatalytic Hydrogen Evolution - Zemeng Wang; Yunsheng Shen; Qingsheng Liu; Tao Deng; Kangqiang Lu; Zhaoguo Hong (Molecules, 2025)
Harnessing abundant and renewable solar energy for photocatalytic hydrogen production is a highly promising approach to sustainable energy generation. To realize the practical implementation of such systems, the development of photocatalysts that simultaneously exhibit high activity, cost-effectiveness, and long-term stability is critically important. In this study, a Cd0.8Zn0.2S nanowire photocatalytic system decorated with graphene (GR) was prepared by a simple hydrothermal method. The introduction of graphene increased the reaction active area of Cd0.8Zn0.2S, promoted the separation of photogenerated charge carriers in the semiconductor, and improved the photocatalytic performance of the Cd0.8Zn0.2S semiconductor. The results showed that Cd0.8Zn0.2S loaded with 5% graphene exhibited the best photocatalytic activity, with a hydrogen production rate of 1063.4 µmol·g−1·h−1. Characterization data revealed that the graphene cocatalyst significantly enhances electron transfer kinetics in Cd0.8Zn0.2S, thereby improving the separation efficiency of photogenerated charge carriers. This study demonstrates a rational strategy for designing high-performance, low-cost composite photocatalysts using earth-abundant cocatalysts, advancing sustainable hydrogen production.